The Urgency, Strategies, and Problems of Mastering Arabic Language for Islamic Preaching Communication - Burhanuddin (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This study aims to examine the urgency, strategies, and problems in mastering the Arabic language for Islamic preaching communication. The focus of the research is on the students of the Faculty of Dakwah at Universitas Islam Negeri (UIN) Jakarta. Mastery of Arabic is considered crucial as it is the primary language of Islamic literature, which is fundamental to preaching activities. The research employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The findings indicate that mastering Arabic is essential for enhancing understanding and effectively conveying Islamic messages. The strategies employed by students include formal classroom learning, self-study, and participation in extracurricular programs related to the Arabic language. However, students face various challenges, such as time constraints, lack of resources, and less varied teaching methods. The study recommends improving the quality of Arabic language teaching through more interactive methods and providing adequate resources to support learning. These findings provide insights for the development of a more effective Arabic language curriculum and learning strategies in Islamic higher education institutions.